Clinical Features, Prognosis, and Long-Term Response to Ranibizumab of Macular CNVs in Pattern Dystrophies Spectrum: A Pilot Study - Lorenzo Casillo; Stefano Tricarico; Laura Contento; Enzo M. Vingolo (Journal of Ophthalmology)
Introduction. To analyze the morphological and functional features of choroidal neovascularizations (CNVs) in eyes affected by pattern dystrophies (PD), evaluating their long-term response to intravitreal ranibizumab, and comparing them with CNVs in age-related macular degeneration (AMD). The mean goal is to identify possible disease biomarkers and to evaluate the long-term prognosis of CNVs in PD. Materials and Methods. A retrospective study of 42 patients with naïve CNV (26 PD and 16 AMD), for a total of 47 eyes (29 eyes in the PD group and 18 eyes in the AMD group). Each patient received a loading dose of ranibizumab (one monthly for three months) followed by pro re nata (PRN) reinjection protocol for a period of at least three years. Morphological OCT parameters (CRT, central retinal thickness; SRF, subretinal fluid; IRF, intraretinal fluid; SHRM, subretinal hyperreflective material; HRF, hyperreflective foci; HCD, hyperreflective crystalline deposits; cCT, central choroidal thickness; slCT, sublesional choroidal thickness; EZd, ellipsoid zone disruption; and best corrected visual acuity (BCVA in logMAR scale)) were reported at baseline and last follow-up. Results. At baseline, no significant differences were found between the two groups, except for choroidal thickness parameters that were significantly greater in the PD group (p = 0.009). Longitudinal PD analysis demonstrated reduction in BCVA (p = 0.009), decrease in CRT (p = 0.046), resolution of SRF in 61.6% of cases (p = 0.004) and SHRM in 30% (p = 0.034), and choroidal thinning both centrally (p = 0.004) and sublesional (p = 0.011) compared to baseline. At 3 years, the PD group received significantly more injections than the AMD (p = 0.011) and showed significantly thicker choroid (p = 0.033) and more frequent HRF (p = 0.006). Regarding the PD group, we found a negative correlation between age and choroidal thicknesses at baseline and at 3 years (p < 0.05); significant positive correlations were found between baseline BCVA and at 3 years (p < 0.001), BCVA at 3 years and IRF (p = 0.003) and SHRM at 3 years (p = 0.003); CRT baseline and CRT 3 years (p = 0.017); HCD at 3 years was associated with greater CRT (p = 0.04) and IRF at 3 years (p = 0.019). Conclusions. Early and long-term morphofunctional features of CNVs in PD and in AMD are overlapping. CNVs in PD have poorer long-term response to ranibizumab and higher choroidal thickness suggesting different pathogenetic and evolutionary mechanisms.